2021
DOI: 10.1101/2021.12.01.470263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rethinking Margin of Stability: Incorporating Step-To-Step Regulation to Resolve the Paradox

Abstract: Maintaining frontal-plane stability is a major objective of human walking. Derived from inverted pendulum dynamics, the mediolateral Margin of Stability (MoSML) is frequently used to measure people’s frontal-plane stability on average. However, typical MoSML-based analyses deliver paradoxical interpretations of stability status. To address mediolateral stability using MoSML, we must first resolve this paradox. Here, we developed a novel framework that unifies the well-established inverted pendulum model with G… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
(172 reference statements)
1
4
0
Order By: Relevance
“…Recently, Dingwell and Cusumano (2019) proposed a ML multi-objective control of normal human gait and showed that the system primarily controls step width and, in a lesser extent, the ML displacement of the centre of mass to regulate walking. These results were latter experimentally confirmed under visually or physically disturbed walking (Kazanski et al, 2020(Kazanski et al, , 2021Render et al, 2021). In this context, step width and ML displacement of centre of mass were more variable but more tightly regulated when walking with continuous lateral oscillations of the visual field, and even more when walking with continuous lateral oscillations o f the support, in comparison with no perturbation (Kazanski et al, 2020).…”
Section: Introductionsupporting
confidence: 56%
“…Recently, Dingwell and Cusumano (2019) proposed a ML multi-objective control of normal human gait and showed that the system primarily controls step width and, in a lesser extent, the ML displacement of the centre of mass to regulate walking. These results were latter experimentally confirmed under visually or physically disturbed walking (Kazanski et al, 2020(Kazanski et al, , 2021Render et al, 2021). In this context, step width and ML displacement of centre of mass were more variable but more tightly regulated when walking with continuous lateral oscillations of the visual field, and even more when walking with continuous lateral oscillations o f the support, in comparison with no perturbation (Kazanski et al, 2020).…”
Section: Introductionsupporting
confidence: 56%
“…In other words, the step-to-step stability required high demands in controls to actively resolve the sensory-conflicted conditions in both anterior-posterior and medial-lateral directions (Hu and Chien, 2021) when either bilateral or unilateral vestibular vibration was provided. Additionally, in the current study, step-to-step stability required even higher demands in controls to counter the instability (Kazanski et al, 2021) induced by the above-mentioned vestibular illusion in the medial-lateral direction when unilateral vestibular vibration was provided than when bilateral vestibular vibration was provided.…”
Section: Mos Measure Could Understand Another Aspect Of Motor Control...mentioning
confidence: 53%
“…Therefore, we speculated that this vestibular illusion caused by unilateral mastoid vibrations required extra effort for CNS to process and eventually increase the MOSml, particularly on the side of the dominant leg (more discussion can be found in Using Dominant Leg to Control the Margin of Stability in the Medial-Lateral Direction). Also, a non-yet-certified peer-reviewed study (Kazanski et al, 2021 ) proposed a probability of instability to predict the instability risk related to MOSml. This previous study had an agreement with the current study that a larger mean MOSml could be a sign of increased risk of lateral instability.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, dynamic postural stabilities when landing the swing foot on the target were investigated with the average data of the MOS across trials, showing that stepping onto the medial target became more destabilized. Recently, Kazanski et al (2021) suggested that an average of the MOS may not be insufficient for evaluating the potential risks of instability ( Kazanski et al, 2021 ). Instead, they proposed that the possibility of instability (POI) that predicts the likelihood of becoming unstable on any future step is more plausible.…”
Section: Discussionmentioning
confidence: 99%